0435 The Relationship Between Pathogen Avoidance and Insomnia Symptoms: Results from a Longitudinal Study Conducted During the COVID-19 Pandemic. (25th May 2022) - Walker, Jamie; Makhanova, Anastasia; Egeler, Mara; Vargas, Ivan
Abstract: Introduction: Pathogen avoidance has intensified during the past two years because of fear related to the high transmissibility of SARS-CoV-2. This trend aligns with previous research that found increases in pathogen avoidance as a result of impaired immune system functioning, such as in the case of autoimmune disease. Another link to compromised immunity is the presence of insomnia symptoms, which may interfere with a healthy immune response to pathogens. It is not clear, however, if insomnia could be an immuno-compromising factor that leads to a compensatory increase in pathogen avoidance. Therefore, the purpose of the present study was to explore the relationship between situational pathogen avoidance and insomnia symptoms during the COVID-19 pandemic. Methods: A national online survey was conducted at two time points: April-June 2020 (baseline) and January-March 2021 (follow-up). Insomnia symptoms were assessed using the Insomnia Severity Index (ISI). Affective, cognitive, and behavioral responses that comprise pathogen avoidance psychology, especially as it pertains to avoidance of potentially pathogenic social stimuli, were assessed with the Situational Pathogen Avoidance (SPA) scale. Results: 2, 980 adults (mean age = 47 years) completed both surveys. Overall, the means on the SPA scale at both time points were higher than previously published norms (mean at both timepoints = 5.4), suggesting that average pathogen avoidance increased since the onset of the pandemic. The mean differences in the SPA scale varied by insomnia symptoms (at both time points), with participants who endorsed clinically elevated insomnia (ISI >14) reporting higher pathogen avoidance (baseline, F(1, 2972) =10.4, p = 0.001; follow-up, F(1, 2918) =26.6, p < 0.001).The mean differences in the SPA scale by insomnia were greater at follow-up compared to baseline (mean difference at baseline = 0.19; mean difference at follow-up = 0.33). This suggests that, compared to the initial months of the pandemic (Apr–June 2020), the relationship between insomnia and situational pathogen avoidance was stronger post-pandemic peak (Jan–Mar 2021). Conclusion: Our findings suggest that there is a positive correlation between insomnia symptoms and situational pathogen avoidance. Furthermore, results indicated that this relationship became stronger as the pandemic went on. Support (If Any): K23HL141581 (PI: Vargas); R25HL10544 (PI: Jean-Louis); K24AG055602 (PI: Perlis)